2019
DOI: 10.1111/tbed.13153
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus strains infecting Swedish domestic pigs are unique for each pig farm and remain in the farm for at least 2 years

Abstract: Hepatitis E virus (HEV) genotype 3 (HEV3) is distributed globally and infects both humans and animals, mainly domestic pigs and wild boars, which are the major reservoirs. In this study, the prevalence of HEV among Swedish pigs was investigated by HEV RNA analysis in 363 faecal samples from 3‐month‐old piglets sampled twice (2013 and 2014) in 30 Swedish pig farms. Four different types of farms were investigated; organic, conventional closed (keeping the sow), satellites in a sow pool (conventional farms sharin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
3
15
0
Order By: Relevance
“…After depopulation of some rooms in the building housing HEV-positive growers, the virus was still detected afterwards. In previous studies (Kantala et al, 2015;Wang et al, 2019;Widen et al, 2011), the persistence of the same virus on farms was confirmed for up to 4 years but in our study this persistence lasted even longer (from 2012). The results of our study partially confirmed recent conclusions obtained by mathematical models designed to predict the length in time of HEV persistence on pig farms (Salines et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…After depopulation of some rooms in the building housing HEV-positive growers, the virus was still detected afterwards. In previous studies (Kantala et al, 2015;Wang et al, 2019;Widen et al, 2011), the persistence of the same virus on farms was confirmed for up to 4 years but in our study this persistence lasted even longer (from 2012). The results of our study partially confirmed recent conclusions obtained by mathematical models designed to predict the length in time of HEV persistence on pig farms (Salines et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…The probability of an individual to become infected by a pathogen is dose dependent and related to route of exposure. For oral ingestion, Bouwknegt et al estimated the dose at which the probability of infection equals 50% at 1.4 * 10 6 HEV genomic copies (PI 50 ) [25]. Andraud et al reported similar results after orally inoculating twelve pigs with different doses, ranging from 10 4 to 10 8 HEV copies.…”
Section: Susceptibility (Dose-response Relationship)mentioning
confidence: 97%
“…Phylogenetic analyses of HEV strains indicate on-farm persistence for two reasons. Firstly, farms often have a unique HEV strain, which can be seen in phylogenetic trees as a separate cluster for every farm [6,72,73]. Secondly, even multiple strains sampled from the same farms, with a long sampling interval, are often closely related [6,72].…”
Section: Persistence Of Hev On Farmsmentioning
confidence: 99%
See 2 more Smart Citations